Martin Buber: guide for a psychology of suffering - Tweed, Roger G.; Bergen, Thomas P.; Castaneto, Kristina K.; Ryder, Andrew G. (Frontiers in Psychology, 2023)
Martin Buber was untrained in psychology, yet his teaching provides helpful guidance for a psychological science of suffering. His ideas deserve attention at three distinct levels. For each of these, his ideas align with research findings, but also push beyond them. At the individual level, Buber’s radical approach to relationships disrupts typical social cognitive cycles of suffering and can thereby build a defense against suffering. At the community level, he provides guidance that can help create a society that cares for people who suffer. At the dyadic level, Buber’s guidance also matters. His ideas point toward a therapeutic dyad that can help address suffering when the individual and community responses are not sufficient. Specifically, he guides us toward a holistic view of the person that transcends labels and also toward ineffable human relations. Here again, his ideas align with empirical research, but push beyond. Buber’s unique take on relationships has much to offer scholars seeking to understand and alleviate suffering. Some might perceive Buber as ignoring evil. That possible criticism and others deserve consideration. Nonetheless, readiness to adjust theory in response to Buber and other psychological outsiders may be valuable when developing a psychology of suffering.